EFEKTIVITAS PELAYANAN SIAP MELAYANI MASYARAKAT MALAM HARI (SIMMAMAH) DI KECAMATAN TAMAN KABUPATEN SIDOARJO - Hena Haudli Zarli; Singgih Manggalou (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
Taman District provides one of the public service innovations in carrying out population administration, namely the Ready to Serve the Community at Night (SIMMAMAH) program. The SIMMAMAH program was formed and created as a way out of the phenomenon that has occurred in Taman District, namely that people do not have time to carry out population administration during working hours or school hours. This innovation program has been adapted to the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 91 of 2021 concerning the Development of Public Service Innovation. The aim of this research is to measure the effectiveness of SIMMAMAH services in Taman District, Sidoarjo Regency. The sampling techniques used were purposive and snowball. Data collection in this research used was observation, interviews and documentation and data analysis used included data collection, data consolidation, data presentation, as well as drawing conclusions and verification. The results of this research are that SIMMAMAH services have been runninf effectively, although not yet perfect. Due to the obstacles found in these services, namely the lack of availability of KTP forms, damaged KIA printers, village/subdistrict networks that do not use Telkom Orbit and not all villages/subdistricts have KTP recording devices.